(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this retrospective study was to evaluate the effects of Diabetes Mellitus on peri-implant marginal alveolar bone loss in sinus lifted well-controlled diabetic patients at long term.Materials and Methods: Thirty eight patients with 77 dental implants were included the study. The study consists of 2 groups; control group (C) and diabetes mellitus group (DM). The dental implants were placed after open window maxillary sinus lifting surgery at maxillary posterior region. After conventional loading process patients were followed periodically for bone loss and clinical parameters. The peri-implant marginal bone loss was assessed at minimum 3 years after functional loading. Standardized panoramic radiographs were obtained at the baseline and maintenance which were used for evaluating the marginal bone loss and clinical and anatomical crown to implant ratio. The Student-t test and Mann Whitney-U test were used to analyse any significant differences between two groups (p0.05). The Kruskal Wallis test was used for inter-group comparisons of parameters and Chi-square test, Fisher’s Exact Chi-square test and Continuity (Yates) correction were used to compare qualitative data. Spearman’s rho correlation analysis was used to examine the relationships between parameters with non-normal distribution.Results: A total of 77 dental implants were followed up for at least 36 months. The mean follow-up was 43.47±10.30 months. 2 implants were failed in DM group. The mean marginal bone loss in DM and C group were 1.35±1.22 mm and 0.91±1 mm respectively. There was no statistically significance in terms of marginal bone loss between the two groups (p>0.05).Conclusion: Within the limitations of this study, it was shown that long-term follow-up results of dental implants in well-controlled diabetic patients were similar to those of healthy individuals and DM did not increase the peri-implant marginal bone loss.